Applying baseflow approach to the environmental flow needs of the Similkameen River Watershed in British Columbia, Canada - Hongli Chen; Qiang Li; Qiaoqiao Wang; Xuanjiao Chai; Yaping Wang (Journal of Hydrology: Regional Studies)
Study region: The Similkameen River Watershed, an international basin, with a substantial portion located in British Columbia, Canada. It is a tributary to the Columbia River, which is the heavily regulated watershed in North America. Study focus: Assessing Environmental Flow Needs (EFN) is imperative for preserving the socio-ecological balance and sustainability. The EFNBF method using baseflow as an index for EFN settings, addresses key challenges faced by conventional methods. In this study, we used discrete conductivity data in the upper, middle, and lower reaches of the watershed to estimate long-term daily conductivities from 1966 to 2017. These facilitated deriving the watershed-level baseflow index (BFI) using conductivity mass balance method, which was subsequently applied to calibrate Eckhardt's BFImax parameter. Using calibrated Eckhardt method, baseflow for 23 tributaries were derived allowing for quantification of EFN for spring, summer and fall-winter across tributaries by the EFNBF method. New hydrological insights for the region: This study presents a reliable scheme for evaluating EFN based on a baseflow calculation using discrete conductivity data. The impacts of licensed water usage on the EFN in the watershed were examined in three tributaries, revealing that current licensed withdrawals exceed water availability during the fall-winter. This suggests more measures are needed to alleviate water stress and ensure the protection of EFN. Therefore, our established EFN can serve as the preliminary estimates of the Similkameen River Watershed for promoting river health and sustainable water management.